Effects of Biostimulant Treatments on Amino Acid Content of Tomato Seedling under Water Deficit (Proceedings of the International Conference on Agriculture, 2022)
In this study, the effect of biostimulant treatment against water stress in tomato seedling period was investigated. In the study conducted in the greenhouse conditions, water stress was applied in two different levels; full irrigation (100% of the field capacity) and 50% of the field capacity. The product used as a biostimulant has 1%Zn, Bacillus subtilis, Bacillus megaterium, Azosprillum and Bacillus amyloliquefaciens (1x109 cfu/ml) content. The solutions prepared at a ratio of 1/10 and 1/5 and were given to the plants three times with one-week intervals. The effects of water stress and biostimulant treatments on amino acid content in tomato seedlings were investigated. As a result of this study, some of the amino acid content in the plant leaf with has increased and some have decreased under different water availability conditions according to the amino acid type. However, depending on the application doses, it was seen that the negative effect of water stress on the amino acid content was alleviated. As a result of the current study, the effect of applications in reducing the damage caused by water stress on tomato seedlings may also be important in terms of amino acid content.
Keywords: amino acid content; drought stress; tomato seedling; bio-stimulant